“Los Conflictos De Las Relaciones Interpersonales Y Su Influencia En El Comportamiento De Los Docentes De La Unidad Educativa Quevedo De La Provincia De Los Ríos. - Tixe Saquinga.Lidia (2015)
Through this research is aimed to contribute to the good life and eliminate conflicts in interpersonal relationships and their influence on the behavior of teachers, based on the research of interpersonal relationships and how they affect the performance of their educational activities. Therefore it has been established as a standard in this study, the relationship that is practiced in one of our educational communities. The research is conducted with the belief that teachers are the mirror in which you look at the students and if they are negative relationships between teachers, these events will affect the behavior of the same. This paper considers relationships as a cornerstone in the process of behavior considering that it will lead to improving the quality of education, based on the study of living well. Much has been written about the teachers, but a research project which addresses the relationships and the influence of these on the behavior of learners, is a work that has not been done, despite the educational work is is closely linked with the history of mankind. From this premise we have considered why the teaching profession is, without doubt, one of the activities that has led to a variety of research and thoughts on the history of universal thought. No matter what the names under which defined this practice: teacher, professor, teacher or teacher.